The Shift From Legal Certainty to Legal Utility in Indonesia’s Non-Conviction-Based Asset Forfeiture Regime - Vincentius Patria Setyawan (Jurnal Hukum Caraka Justitia, 2026)
This article analyzes the shift in legal approach to addressing assets derived from corruption in Indonesia, from an orientation toward legal certainty to an emphasis on legal utility through the mechanism of non-conviction-based asset forfeiture (NCB). The research employs a normative juridical method using statutory, conceptual, and comparative approaches, supported by a literature review of national regulations, court decisions, and international practices, particularly in the United States and Australia. The findings indicate that NCB serves as an effective alternative instrument for recovering corruption-related assets that cannot be reached through conventional criminal proceedings, especially in cases where the perpetrator has died, fled, or cannot be held criminally liable. Although its implementation raises debates concerning legal certainty and the protection of property rights, this utility-based approach is considered more adaptive in supporting anti-corruption efforts and the recovery of state losses. Therefore, this study concludes that strengthening the national regulatory framework is necessary to balance substantive justice with the protection of human rights.